The Development of Subject Gateway and Library Operating Model for the Diffusion of Entrepreneurship – Job and Employment Services - PARK, OK NAM (International Journal of Knowledge Content Development & Technology, 2021)
High unemployment rates repeatedly cause recurring social problems such as fewer employment opportunities and employment insecurity. Following this trend, various programs related to employment have been provided through various government and institutions. However, they have established overlapping policies and programs and there is no one stop gateway to find effective and efficient way to find relevant information. For this purpose, this study aims to provide employment and job search subject gateway development. The study has carried out case studies, literature reviews, and user survey. Based on this study, it suggested a linked metadata model to organize and link scattered information together, and a digital gateway operating diverse information services. It is expected to provide a basis to develop comprehensive information service model for employment. URL: http://ijkcdt.net/xml/28317/28317.pdf